An ordered mesoporous hydroxyapatite: Preparation, loading, and sustained releasing to ciprofloxacin. Issue 4 (25th December 2022) - Ma, Ke; Gao, Yuli; Yi, Jianjun; Cui, Meng; Hao, Haijun; Xu, Qinghong
Abstract: A kind of new mesoporous hydroxyapatite (noted as mesoHA) with about 2.4 nm average porous diameter was successfully prepared by casting Ca 2+ and H2 PO4 − ions on the inner channel surface of Si‐MCM‐41 and dissolving the Si‐MCM‐41 in alkali soluble, and the porous material was used as a pH‐responsive platform to adsorb and release ciprofloxacin molecules. A maximum mass of 0.51 mg of ciprofloxacin (noted as Cip) was loaded on 1.00 mg of the host, and the release rate of the drug was found increasing with the acidic increase of the external solution environment (based on the stability of mesoHA) that simulated basic composition to human plasma. About 88.5% of Cip was released from the platform when environmental pH value was about 4.8, which provides a new method on utilizing antibiotics drugs efficiently, for the host mesoHA is friendly to human body.